Effectiveness of Video-Based Preoperative Education on Reducing Anxiety Levels in Patients Undergoing Surgery: A Literature Review - Siti Suryani Asmara; Yanuar Primanda; Fitri Arofiati (Indonesian Journal of Global Health Research, 2026)
Preoperative anxiety is a psychological response frequently experienced by patients prior to surgical procedures and can have negative impacts on physiological conditions, anesthetic requirements, and the postoperative recovery process. Video-based preoperative education is considered an innovative approach that is potentially more effective than conventional educational methods. This literature review aims to analyze the effectiveness of video-based preoperative education on reducing anxiety levels in patients undergoing surgical procedures. This study utilized a literature review design with a systematic article search conducted on PubMed, Scopus, and ScienceDirect databases. The included articles were quantitative studies with randomized controlled trial and quasi-experimental designs published between 2020–2025. Out of 1,487 articles, 11 articles that met the inclusion criteria were analyzed narratively. The review results indicated that all studies reported a significant reduction in preoperative anxiety levels in groups receiving video-based education compared to conventional education or no intervention. Video education was proven to improve understanding, a sense of security, and the psychological readiness of patients before surgery. Video-based preoperative education is effective in reducing patient anxiety levels and has the potential to be integrated into standard preoperative care.